Conjoined Twins Having Cranio-Thoraco-Omphalopagus along with Mild Polyhydramnios (Community Based Medical Journal, 2025)
Conjoined twins, sometimes known as Siamese twins, are a rare kind of congenital human malformation. Conjoined twins are an extremely rare and rarely encountered impediment to monozygotic twinning, occurring in 1 in 100,000 to 1 in 250,000 live births. Conjoined twins share the same genes and are of the same sex. Reports have indicated a 3:1 female predominance. A 17-year-old woman at 23 weeks of gestation was referred at her second trimester of pregnancy from a rural area. Ultrasonographic evaluation revealed the presence of a monochorionic, monoamniotic twin pregnancy. The twins conjoined with a single face, single thorax and abdomen with separate upper limb and lower limb. It was finally diagnosed as a case of cranio-thoraco-omphalopagus conjoined twins of about 23±1 weeks with mild polyhydramnios. A conjoined twin is a well-known rare entity. It is very important to make a diagnosis by ultrasound in time to prevent future complications. Thoraco-omphalopagus type is known to present several cardiac anomalies. Thus, early diagnosis of conjoint twins, details of organ sharing by imaging modalities will help to predict prognosis, aid in patient counseling and further management.  CBMJ 2025 January: Vol. 14 No. 01 P: 172-176